GE_GERICHTE C/25704/2017 vom 4. Februar 2020 - GE Cour de justice (2020)
ASSEMBLÉE GÉNÉRALE;DÉCISION;ACTION EN NULLITÉ(EN GÉNÉRAL);INVITATION;QUALITÉ POUR AGIR ET RECOURIR | CPC.59.al2.leta; CO.689.al1; CO.700.al1; CO.706.al1; CO.706.letb.ch1